The Promoting Effects of 2, 3, 7, 8-Tetrachlorodibenzo-p-Dioxin on Nasal Tumors in Sprague-Dawley Rats - R Wasito (Indonesian Association of Food Technologists, 1994)
It was hypothesized that exposure to environmentally relevant dietary levels of 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin (TCDD) or 2, 2', 4, 4', 5, 5'-hexachlorobiphenyl (245- HCB) could cause the development of nasal tumors and a combined exposure to these compounds could have a potentiating effect on tumor development. Thirty days after partial hepatectomy and NDEA administration, groups of 12 or 24 female Sprague-Dawley rats were fed a basal diet or diets containing 10 ppt TCDD, 10 ppt TCDD, 5 ppm 245-HCB, 10 ppt TCDD and 245-HCB or 100 ppt TCDD and 245-HCB for 140 days. Basal diets were fed from day 140 unit rats were killed on day 210 or day 420. Results indicated that TCDD or a combination of TCDD and 245-HCB significantly increased the incidence of nasal tumors by day 420. However, a combined exposure to TCDD and 245-HCB had no potentiating effect on the incidence of nasal tumors.